Transnational space between women’s NGOs in Germany and Turkey: Current situation and future expectations - Aliefendio?lu, Hanife (Taylor and Francis, 2017)
One of the most important social phenomena to occur over the last 50 years is that of international migration. In 1961, Turkish workers began to migrate to Germany in accordance with the bilateral agreement between Turkey and Germany.1 In 1975, 80 percent of the Turkish migrants living in Europe had emigrated to Germany (Kadioglu, 1997, p. 538; Caglar, 1995, p. 309). Turkish migrants now make up 28 percent of the foreign population in Germany, and are thus the largest group of foreigners living in that country (FGCFI, 2000, p. 7). According to information from the German Ministry of Employment, the total Turkish immigrant population in Germany is 2,110,223 (1,145,057 of whom are men, whilst 965,166 are women). The largest subgroup consists of people between the ages of 15 and 29 (316,073 women and 365,643 men) (YGB, 2000, p. 9). 400,174 men and 170,474 women are in paid employment (YGB, 2000, p. 12). In 1960, the number of migrant female workers was just 173, however by 1974, the number had increased to 159,984 (SPO, 1994, p. 106). © Thomas Faist and Eyüp Özveren 2004.